Current controversies in philosophy of religion - Draper, Paul (ed.)
While orthodox religion by its very nature is conservative, philosophy at its best is inherently radical. It challenges authority, tradition, and the whole idea of "dogma." For this reason, philosophy of religion can be explosively controversial. It is bound to disturb those who peddle incontrovertible truth and fascinate those who seek spiritual truth and are willing to follow the argument wherever it leads. This volume is designed for such seekers. It brings together an international team of leading philosophers of religion to explore and debate radical new ideas about religion, God, and ultimate reality.
Includes bibliographical references and index.
Keywords: Religion